PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BAGIAN PEREKONOMIAN SDA DAN ADMINISTRASI PEMBANGUNAN SETDA KABUPATEN MALUKU TENGAH - Hendry Ch. Soselisa (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2020)
This study aims to examine the effect of work environment and work motivation on employee performance. The population in this study were all 26 employees at the SDA Economic Affairs and Development Administration Office of Central Maluku Regency, totaling 26 employees who were used as research respondents and did not use samples. The results showed that the work environment had a significant effect on employee performance while work motivation had a significant effect on employee performance.